Effects of career guidance, internship experience, emotional intelligence, and soft skills on students’ work readiness - Reno Fitlova Chaspi; Usmeldi Usmeldi; Dedy Irfan; M. Giatman (Journal of Educational and Learning Studies, 2026)
This study aimed to examine the effects of career guidance, internship experience, emotional intelligence, and soft skills on the work readiness of students at SMKN 7 Sijunjung. This study employed a quantitative correlational design involving 73 twelfth-grade students selected using purposive sampling. Data were collected through Likert-scale questionnaires and analyzed using descriptive statistics, assumption tests, simple and multiple regression analyses, t-tests, F-tests, and coefficients of determination. The results revealed that career guidance, internship experience, emotional intelligence, and soft skills each had positive and significant effects on work readiness, contributing 21.6%, 35.3%, 20.2%, and 24.7%, respectively. Simultaneously, these variables explained 46.2% of the variance in work readiness. These findings indicate that strengthening educational support and personal competencies is essential for enhancing vocational students' readiness for employment.